(untitled) (NAU Journal of Technology and Vocational Education, 2026)
This study investigated product packaging as a predictor of emotional buying and price sensitivity among business education undergraduates in public universities in Anambra State, Nigeria. A correlational survey research design was adopted, and a multi-stage sampling technique involving proportionate stratified and convenience sampling was used to select 119 respondents from a population of 535 students. A structured and validated questionnaire was used to collect data, with reliability indices of .841, .792, and .880 for the respective clusters. Data were collected via Google Forms and analyzed using SPSS Version 23.0, employing Pearson Product Moment Correlation and simple linear regression. Results revealed that product packaging does not significantly predict emotional buying or price sensitivity among the students. This indicates that visual and design elements of product packaging may not strongly influence either emotionally-driven or price-sensitive purchase decisions in this context. It is recommended that brands emphasize value communication and emotional storytelling through packaging to enhance consumer response.